2021
DOI: 10.1016/j.jbc.2021.101157
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of the myosin super-relaxed state and interacting-heads motif in solution

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 23 publications
(47 reference statements)
4
43
0
Order By: Relevance
“…The opposite of what might be expected if the thick filament stabilizes the SRX form of myosin. In a recent paper, Chu et al (2021) ( 20 ) also reported a mismatch between estimates of the fraction of myosin heads in the SRX state and the IHM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite of what might be expected if the thick filament stabilizes the SRX form of myosin. In a recent paper, Chu et al (2021) ( 20 ) also reported a mismatch between estimates of the fraction of myosin heads in the SRX state and the IHM.…”
Section: Discussionmentioning
confidence: 99%
“…Work on isolated skinned muscle fibers, myofibrils, myosin thick filaments, heavy meromyosin (HMM), and myosin has revealed the presence of two populations of “relaxed” myosin heads ( 16 , 18 , 19 , 20 ). Those with the typical ATPase turnover rate of a single isolated motor domain (0.05 s-1), and a second population with a much slower turnover rate (∼0.005 s-1) the SRX population.…”
mentioning
confidence: 99%
“…They hypothesized that myosin heads can occupy an SRX without adopting a folded IHM conformation that is further stabilized by intramolecular interactions similar to those existing in the IHM ( 20 ). Additional support comes from time-resolved fluorescence resonance energy transfer experiments showing that the SRX can exist in the absence of a conventional IHM, suggesting that the IHM is sufficient but not necessary to produce the SRX kinetic state ( 41 ). The molecular pathogenesis of DCM was recently assessed in the context of the myosin SRX state and IHM paradigm ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the myosin motors are not immediately available for interaction with actin, as they are folded into helical tracks on the surface of the thick filament in an asymmetric conformation called the “interacting heads motif” ( Zoghbi et al, 2008 ; AL-Khayat et al, 2013 ), which was first identified in smooth muscle myosin ( Wendt et al, 2001 ) and in isolated thick filaments from skeletal muscle of the tarantula ( Woodhead et al, 2005 ). This folded conformation is assumed to inhibit actomyosin interaction and myosin adenosine triphosphatase, locking the myosin motors in an energy-saving state that has been identified with the “super-relaxed state” observed biochemically ( Stewart et al, 2010 ; Hooijman et al, 2011 ), although other factors may also modulate that state ( Chu et al, 2021 ). Recent studies on cardiac muscle using x-ray diffraction ( Reconditi et al, 2017 ; Brunello et al, 2020 ) and fluorescent probes on myosin ( Park-Holohan et al, 2021 ) showed that in the resting phase of the cardiac cycle between beats, called “diastole,” the myosin motors are folded onto the thick filament surface in a conformation consistent with the interacting heads motif.…”
Section: Introductionmentioning
confidence: 99%